Ferulic acid mitigates 3-Nitropropionic acid-induced Huntington’s disease via modulation of Nrf2/HO-1, TLR4/NF-κB, and SIRT1/p53 signaling pathways - Abdelgawad, Mohamed A.; Gendy, Abdallah M.; Zaghlool, Sameh S.; Elesawy, Wessam H.; Ragab, Mai F.; Kotb El-Sayed, Mohamed I.; El-Haddad, Alaadin E.; Mohamed, Hussein S.; Alsalahat, Izzeddin; Essa, Marwa A. (Frontiers in Pharmacology, 2025)
BackgroundFerulic acid (FA) is a natural phenolic compound that has demonstrated effectiveness against Huntington’s disease (HD). However, its exact mechanism remains unclear. Therefore, the current study aims to investigate FA’s potential mechanism of action against 3-nitropropionic acid (3NP)-induced HD.MethodsAdult male Wistar albino rats were administered FA orally (100 mg/kg) for 3 weeks, and 3NP (10 mg/kg) was intraperitoneally administered during the last 2 weeks to induce HD. Behavioral performance was assessed using the open field and hanging wire tests. Striatal tissue was analyzed using ELISA, qRT-PCR, Western blotting, histopathology, and immunohistochemistry.ResultsAdministration of 3NP led to weight loss, neurobehavioral deficits, oxidative damage, apoptotic cell death, and neuroinflammation. FA treatment mitigated these pathological changes by activating Nrf2/HO-1 signaling, a critical player in cellular redox balance. This beneficial effect was mirrored in restoring TAC levels and suppressing MDA. Moreover, FA suppressed TLR4/NF-κB inflammatory signaling, thereby reducing TNF-α and IL-1β levels. In addition, the anti-apoptotic properties of FA were confirmed by modulating SIRT1/p53 signaling, leading to Bcl-2 enhancement and caspase-3 downsizing. Furthermore, FA enhanced neuronal survival and plasticity confirmed by neurotrophic BDNF elevation. Histopathological and immunohistochemical analyses confirmed improved neuronal survival and reduced gliosis following FA treatment.ConclusionThe current research demonstrates that FA exhibits potent neuroprotective effects in experimental HD by modifying Nrf2/HO-1, TLR4/NF-κB, and SIRT1/p53 signaling pathways. These findings provide new mechanistic insights into FA’s potential role in managing HD.